2020
DOI: 10.14744/less.2020.46873
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic gastrostomy: Single center experience

Abstract: Introduction: Percutaneous endoscopic gastrostomy (PEG) is a method used for long-term enteral feeding in patients with normal gastrointestinal function and who cannot be fed orally. In this study, we aimed to present the demographic and clinical features of our patients who underwent PEG. Materials and Methods: The records of patients who had PEG tube inserted in the endoscopy unit or intensive care units in our hospital between August 2017 and December 2019 were reviewed retrospectively in this study. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Sözüer et al [2] , 22.6% of complications were observed in the early period. In the study conducted by Çetin et al [8] , early complications were observed in 13.8% of the patients and late complications were observed in 6.4%. In our study, similar results were found in the literature.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Sözüer et al [2] , 22.6% of complications were observed in the early period. In the study conducted by Çetin et al [8] , early complications were observed in 13.8% of the patients and late complications were observed in 6.4%. In our study, similar results were found in the literature.…”
Section: Discussionmentioning
confidence: 91%
“…PEG is used as a method with low complication risk, inexpensive,and high efficiency in terms of providing long-term nutrition. [8] The most commonly used enteral feeding method is wig gastrostomy. Although PEG has many placement techniques, the pull technique is the most commonly used.…”
Section: Discussionmentioning
confidence: 99%